PERANCANGAN BAHAN AJAR INTERAKTIF BERBASIS ARCS (ATTENTION, RELEVANCE, CONFIDENCE, AND SATISFACTION) UNTUK MENINGKATKAN MOTIVASI BELAJAR SISWA DI SMP 31 PADANG - Sari, Asri Wahyuni; Afrini Rahmi (Kilau Publishing, 2023)
The purpose of this community service activity is to provide knowledge and skills to teachers, especially teachers of Indonesian subjects about writing teaching materials that can increase student motivation in the learning process. This devotion is focused on writing anecdotal text teaching materials based on the ARCS model. This activity was carried out for two months with four stages, the teacher was enthusiastic and followed the training well. The purpose of this service is that teachers write teaching materials that suit student needs based on the ARCS model. This model is also suitable to meet the demands of an independent curriculum that requires increasing student motivation in the learning process.